Nutrition & diagnosis related care - Escott-Stump, Sylvia (Chicago, IL : Academy of Nutrition and Dietetics, 2022)
"This authoritative go-to resource for students and clinical nutrition practitioners covers over 270 conditions in 16 sections. Each section provides an overview followed by essential evidence-based information on nutrition management of each condition. Nutrition therapy and practical guidance is presented in a unique style that is easy-to-navigate and implement in practice. Mini case studies throughout demonstrate application of the Nutrition Care Process and standardized language in a practical example. Comprehensive appendix material addresses basic nutrition principles, dietary supplements, laboratory data assessment, cultural competency, dietetics practice and quality standards, and much more"--
Includes bibliographical references and index.
In English
Keywords: Diet therapy -- Handbooks, manuals, etc; Nutrition disorders - Diet therapy; Nutrition -- Handbooks, manuals, etc